Bridging Faith and Finance: The Role of Financial Literacy and Behavior in Sharia-Compliant Fintech Adoption Among Entrepreneurs in Indonesia - Nabila Hidayati; Hismendi Hismendi; Busra Busra (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study aims to examine the influence of financial knowledge and financial behavior on the interest in using Islamic financial technology (fintech) lending, with Sharia compliance as a moderating variable among MSME (Micro, Small, and Medium Enterprises) entrepreneurs in Lhokseumawe City. This is a field research employing a quantitative descriptive approach. The population comprises 6,352 MSME actors in Lhokseumawe, with samples selected through purposive sampling. A total of 144 respondents were included in the sample. Data analysis was conducted using Structural Equation Modeling (SEM). The results indicate that: (1) Financial knowledge and financial behavior have a positive and significant influence on Sharia compliance; (2) Sharia compliance and financial behavior significantly influence the interest in using Islamic fintech, while financial knowledge does not have a direct effect on fintech usage interest; (3) Sharia compliance fully mediates the relationship between financial knowledge and fint ech usage interest, and partially mediates the relationship between financial behavior and fintech usage interest. These findings highlight the importance of adherence to Sharia principles as a key factor influencing the interest of entrepreneurs in adopting Sharia-based fintech services.